Manajemen Pengembangan Pendidikan Kitab Kuning di Pondok Pesantren Al-Djunaediyah - Nasrullah, Yufi Mohammad; Mutiawan, Dadang; Noorjutstiatini, Witrin; Nazib, Fiqra (Jurnal Pendidikan Agama Islam, 2025)
Al Djunaediyah Garut Islamic Boarding School is an institution deeply rooted in the rich tradition of Islamic education in Indonesia. Among its primary educational pursuits, the study of "kitab kuning" (classical Islamic texts) holds a prominent place. Kitab kuning, composed of a collection of classical Islamic works, serves as the foundational source of knowledge for Islamic theology, jurisprudence, and Arabic culture. Thus, the development of kitab kuning instruction at Al Djunaediyah Garut Islamic Boarding School plays a pivotal role in preserving and propagating the intellectual heritage of Islam. The evolution of kitab kuning education is an ongoing challenge, requiring comprehensive management encompassing curriculum development, teaching methods, resource allocation, and assessment procedures. Effective management is the cornerstone of ensuring that kitab kuning instruction thrives within the institution. This article delves into the management of kitab kuning education at Al Djunaediyah Garut Islamic Boarding School. It explores the background, underscores the significance of kitab kuning education, and elucidates how effective management practices can sustain and enhance the quality of kitab kuning instruction in this venerable institution. As the digital era brings about profound changes in educational paradigms, the school must continuously adapt its pedagogical approach to remain relevant and effective in transmitting Islamic knowledge to the younger generation. Therefore, the continued development of kitab kuning education is of paramount importance, ensuring that the invaluable intellectual legacy of Islam perseveres and thrives in the face of modern challenges. Keyword: Managing, Yellow Book Education, Islamic Boarding School.